ANALISA DETEKSI GAMBAR TERMODIFIKASI DENGAN DEVIASI RGB - Heriyanto Heriyanto (Jurusan Teknik Informatika, 2013)
Saving picture which one media represent become part of memory or history document. It ispossible that very important to personal. Storage media of picture sometimes become importantthat had been happened a modification about the original picture whitch a document become veryvaluable because change by other people and than It is very difficult to prove will the truth of dataand original picture and modification picture. Modification picture in general to repair or withspecific purpose become the picture makes wrong purpose. BRG picture ( Blue Red Green)representing base from colour in picture and It can be analyses about the picture change or colouraddition or the picture not change. Process checking of original picture is not also pixel but changeof colour a picture, can be known also with change of original primary colour of picture withadditional colour of picture, so that can be known by effect change of the colour with some analysiswhich can ascertain colour change or not. How big change of the colour can be calculating withuse of primary colour mean, change of blue colour mean, change of green colour mean, change ofmean red and also all of them can be combine.Keywords : History, Color, BRG (Blue, Red, Green), Modification, Document, Picture